(3MSf GdefGbH GdSQjI GdefJRYI ef GdSjQI GdXGgQjI (B((3GdXGgQ HjHQS(B)s - (3TGaY Hf Ydj Hf YHGS Hf ESeGYjd Hf YSGcQ GdcfGfi GdYSbdGfi GdcGJHs; (3eMeO Hf EHQGgje Hf TOGO YR GdOjf GdCfUGQj GdcGJH GdMdHj, CHh Ydj,J (B684 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMjG PcQ Gdedhc s
(3BNQgG (B:s
(3fLRJ GdefGbH GdSQjI GdefJRYI ef GdSjQI GdXGgQjI s
(3GNJUQg ef SjQI Gdedc GdXGgQ HjHQS GdJi CdagG cGJH SQg eMji GdOjf YHOGddg Hf YHOGdXGgQ hcGf GdeDda GdePchQ SCdg GNJUGQgG ai MjGJg ade jJgjC dg Pdc EdG HYO haGJgs
(3UhQJ GdfSNI ef NRGfI HGQjS SfI (B1345s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B116 s
Keywords: (3GdJGQjNs